Young people and second chance schools in Spain: diversity of profiles, expectations and results - Rafael Merino; Ana I. Córdoba; Davinia Palomares-Montero; Xavier Alarcon (International Journal of Adolescence and Youth)
Second Chance Schools were created for students without a secondary school certificate. These students are often seen as having similar social profiles and negative school experiences, but this study shows their diversity. A longitudinal study was conducted using two questionnaires at different times with students in Second Chance Schools in Spain. Due to high turnover, the samples partially overlapped: 1,577 students answered the first questionnaire, 1,335 the second, and 744 completed both. The study analyses trainee profiles, changes in expectations from the start to the end of the programme, and perceptions of learning outcomes. The findings reveal varied profiles and interpretations of educational vulnerability, with diverse social backgrounds. Overall, results are positive regarding students’ learning and their evaluation of the training received.